Pengaruh Kepemimpinan Transaksional Guru Melalui Media Pembelajaran Digital Terhadap Kualitas Pembelajaran Siswa - Syahreza, Hadian Firman; Gultom, Syawal; Rosnelli, Rosnelli (STKIP Pesisir Selatan, 2024)
This research aims to analyze the influence of teachers' transactional leadership through digital literacy on the quality of student learning. In today's digital era, a teacher's ability to apply digital literacy in the learning process is crucial for creating a dynamic and participatory learning environment. Teachers' transactional leadership, characterized by active student involvement in decision-making and the freedom to express opinions, is expected to enhance the quality of student learning. The research employed a quantitative survey, with data collected through questionnaires distributed to junior high school students. The study showed that teachers who adopt a transactional leadership style and utilize digital technology in the classroom can increase student motivation, participation, and learning outcomes. Digital literacy becomes a key tool for teachers to deliver more interactive, relevant, and contemporary learning experiences. Therefore, the integration of transactional leadership and digital literacy has a significant impact on improving the quality of student learning. This research suggests enhancing digital literacy training for teachers and encouraging the application of a transactional leadership approach to support better educational quality.